Integrated Proteomic and Metabolomic Analysis of the Testes Characterizes BDE-47-Induced Reproductive Toxicity in Mice - Liang Xu; Songyan Gao; Hongxia Zhao; Liupeng Wang; Yiyi Cao; Jing Xi; Xinyu Zhang; Xin Dong; Yang Luan (Biomolecules, 2021)
A representative congener of polybrominated diphenyl ethers in the environment, 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47), is associated with male reproductive toxicity, yet the underlying mechanisms remain largely unclear. In this study, mice were administered environmentally relevant concentrations of BDE-47 for six weeks. Histopathological observations showed that BDE-47 induced inflammatory reactions and damaged the testes. By conducting an integrated proteomic and metabolomic analysis coupled with a bioinformatic analysis using ingenuity pathway analysis (IPA) methods, we found that BDE-47 mainly affected the molecules involved in free radical scavenging, cell death and survival, neurological disease, and inflammatory response. IPA canonical pathways showed inflammatory and apoptosis pathways, including hepatic fibrosis/hepatic stellate cell activation, the GP6 signaling pathway, tight junction signaling, acute phase response signaling, LXR/RXR activation, unfolded protein response, and FXR/RXR activation, which are related to male reproductive toxicity. Key transcriptional regulator networks were activated via a focus on upstream regulator analysis. The expression of MYC and Clu as the core transcriptional factor and targeted protein, respectively, was verified. It is further proposed that MYC may contribute to the etiology of male reproductive toxicity. These findings will improve our understanding of the mechanisms responsible for BDE-47-induced male reproductive toxicity, which may promote the discovery of useful biomarkers indicative of BDE-47 exposure.